Reproductive patterns of Aratus pisonii (Decapoda: Grapsidae) an estuarine area of Sao Paulo Northern Coast, Brazil - de Arruda Leme, Maria Helena (Universidad de Costa Rica, 1998)
The tree crab Aratus pisanii (H. Milne Edwards 1837) is a tropical sesarminae species widely distributed in the western Atlantic from central Florida to Brazil, arid in the eastem Pacific from Nioaragua to Peru (Melo 1996), being commonly found 00 the upper littoral zone in mangroves.